An Exploratory Cohort Study of the Association between the Level of Testosterone and Suicidal Ideation in Hospitalized Adolescent Females with Depression in China. (27th October 2021) - Liu, Yan; Wang, Shaohua; Xue, Chuang; Hu, Xiwen; Zhou, Guoling; Zhou, Yuanyue; Fang, Dan; Ding, Kaijing
Abstract : Background . To date, around 4 per 100, 000 adolescents committed suicide within the 29 OECD countries. The suicidal behavior is related to psychological factors, genetics, neurobiology, and other biomarkers. The aim of this study was to examine risk factors for the development of suicidal ideation in adolescent females with depression, focusing on the relationship between different testosterone levels and suicidal ideation, in order to help develop strategies to intervene in suicidal behavior in female adolescents with depression. Method . In this single-center prospective cohort study, we enrolled adolescent females with depression. We collected information on their baseline data, testosterone levels, symptom self-rating scale scores, suicidal ideation, non-suicidal self-injurious (NSSI) behaviours, and suicide attempts. We used multivariate logistic regression to identify risk factors for the development of suicidal ideation in adolescent females with depression. Results . A total of 113 hospitalized adolescent females were enrolled with a mean age of 13.5 (1.20). Among these patients, there were 86 (76.11%) subjects who suffered from suicidal ideation, 59 (52.21%) had NSSI and 23 (20.35%) had suicide attempt behavior. In the final model, higher level of testosterone (p = 0.04 ) and higher age (p = 0.02 ) were associated with the higher odds of having suicidal ideation. Conclusion . In this exploratory cohort study, the emergence of suicidal ideation was common among adolescent females with depression. This study is consistent with the other studies. It shows that the age is a potential predictor for suicidal ideation in hospitalized adolescent females with depression.